A Comprehensive Systematic Review of Comparative Outcomes Following Laparoscopic Versus Open Cholecystectomy for Gallbladder Disease: Evidence Synthesis from Randomized Controlled Trials and High-Quality Comparative Studies - Afdhona Wiranata; John M.Sangkai (International Medical Journal Corp. Ltd, 2025)
Introduction Laparoscopic Cholecystectomy (LC) has become the global standard for symptomatic gallbladder disease, replacing Open Cholecystectomy (OC). However, the critical need for continuous, rigorous systematic evaluation across a broad spectrum of clinical, safety, and socioeconomic outcomes persists to validate modern surgical policy, especially for high-risk and complex patients. This review provides a definitive, quantitative synthesis comparing LC and OC. Methods Following PRISMA guidelines, a systematic search identified over 15 high-quality comparative studies, primarily Randomized Controlled Trials (RCTs), published through 2025. Data were extracted for 17 specific outcomes spanning efficiency, safety, morbidity, and cost. Methodological integrity was assessed using the Cochrane Risk of Bias tool (RoB 2.0). Meta-analytical synthesis employed random-effects models to pool comparable outcomes, calculating Risk Ratios (RR) or Odds Ratios (OR) and Weighted Mean Differences (WMD) with 95% Confidence Intervals (CI). Results Laparoscopic Cholecystectomy demonstrated overwhelming superiority in recovery and systemic safety. Key findings include a substantial reduction in Length of Hospital Stay (LOHS) (WMD ≈ -3 days) and accelerated Time to Return to Normal Activity (WMD ≈ -22.5 days) (Cochrane Review, 2007). LC significantly reduced overall morbidity (12% vs 22%) (Kamal, 2025) and provided robust protection against systemic complications, including respiratory (OR 0.55, P < 0.00001) and cardiac events (OR 0.55, P = 0.002), particularly in the elderly (Wang et al., 2014). Economically, LC resulted in lower projected 5-year cumulative charges (Cost-Effectiveness Study, 1993) and markedly fewer sick leaves (OR 0.34, P = 0.01). Discussion The synthesized evidence firmly establishes LC as the standard of care due to its superior short-term clinical benefits, reduced systemic inflammatory stress, and demonstrable economic advantages. The consistent reduction in LOHS and convalescence time translates directly into greater societal productivity. While conversion rates exist (2–10%), they serve as a critical safety valve, preserving the overall low morbidity profile of the laparoscopic approach. Conclusion Laparoscopic Cholecystectomy offers superior clinical outcomes, enhanced patient safety, and a lower overall socioeconomic burden compared to Open Cholecystectomy. LC should be maintained as the primary operative modality for the management of gallbladder disease.